Precipitation of Sodium Acetate Trihydrate from Its Supersaturated Solution - Ahmad, Jamil (Asian Journal of Chemistry, 2010)
The rate of crystallization of sodium acetate trihydrate from a supersaturated solution in water was measured by seeding the solution contained in a 50-cm long tube at one end, and measuring the speed at which the solid-liquid boundary advanced. The rate of crystallization was found to increase directly with the concentration of the solution, in accordance with the equation proposed by Wilson and Frenkel. The rate was found to be independent of the temperature in the range of the concentrations studied. This has been explained in terms of a cancellation of opposite effects: that of the degree of supersaturation on the one hand and of the viscosity and diffusion on the other.